The Priority Tasks of Pediatrics Education and Science in the Health Care Reform - O.K. Tolstanov (Zaslavsky O.Yu., 2013)
In the article listed the main missions for scientists and educators in the context of reforming the current health care for improving the children's health. Attention is paid to the introduction of international experience in providing specialized care to newborns and immunization against infectious diseases. Accentuated existing problems and achievements in providing medical care to children in Ukraine and identified promising areas of pediatric science.